Enquadramentos noticiosos da Gripe Pneumónica na imprensa portuguesa: os casos dos jornais O Comércio do Porto, O Algarve e da revista Ilustração Portuguesa - Helena Lima (2021)
Pandemics are topics of great newsworthiness, given the impact they have on people's lives. Fear, mortality, health measures and medical response are subjects present in the news agenda in the current epidemic crisis. These perceptions were also part of the 1918-1919 disease. Data on the Spanish Flu point to an estimated mortality of between 50 and 100 million people. In Portugal, the disease became better known as Pneumonic Flu or simply Pneumonic and it hit the country in three major waves, starting in May 1918, and ending in 1919. The peak was in October 1918, with mortality figures estimated, ranging from an initial number of around 59,000 dead, and later recalculated in amounts that can reach up to 135 thousand victims. This study tackles the weekly publications Ilustração Portuguesa and O Algarve and the daily O Comércio do Porto, from October 1918 to January 1919, corresponding to the peak of the pandemic. Through a quantitative and content analysis, we seek to identify and interpret the news procedures used by these different publications to cover the Pneumonic Flu. The methodological approach considers the categorizations given by journalistic formats such as genre, prominence and newsvalue, complemented by the identification of standard discursive elements, which produce interpretive frameworks on the part of readers